2012
DOI: 10.1002/cpe.2909
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the Cray XMT and XMT‐2

Abstract: SUMMARYWe explore the comparative performance of the Cray XMT and XMT‐2 massively multithreaded supercomputers. We use benchmarks to evaluate memory accesses for various types of loops. We also compare the performance of these machines on matrix multiply and on three previously implemented dynamic programming algorithms. It is shown that the relative performance of these machines is dependent on the size (number of processors) of the configuration, as well as the size of the problem being evaluated. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This may be due to the problem being too small to afford parallelism for the given number of processors or because of limitations of the memory subsystem of XMT-2. The latter phenomenon has been described in [38], where it was shown that for some XMT codes with intense memory access, it is worthwhile to use fewer than the available number of processors to obtain the best performance. There is a spread in runtimes for large numbers of processors that we explored by running five randomly generated problems for sizes from 500 2 to 8000 2 , for eight processors or more.…”
Section: Performance On Synthetic Imagesmentioning
confidence: 92%
See 2 more Smart Citations
“…This may be due to the problem being too small to afford parallelism for the given number of processors or because of limitations of the memory subsystem of XMT-2. The latter phenomenon has been described in [38], where it was shown that for some XMT codes with intense memory access, it is worthwhile to use fewer than the available number of processors to obtain the best performance. There is a spread in runtimes for large numbers of processors that we explored by running five randomly generated problems for sizes from 500 2 to 8000 2 , for eight processors or more.…”
Section: Performance On Synthetic Imagesmentioning
confidence: 92%
“…The MTA-2 was followed by the XMT (earlier code-named 'Eldorado') [33,34]. The performance of this machine is described in [35][36][37][38].…”
Section: The Cray Xmt-2mentioning
confidence: 99%
See 1 more Smart Citation